The Impact of Nanomaterials on Improving the Efficiency of Solar Cells: A Modern Analytical Study (مجلة العلوم الشاملة, 2025)
Nanomaterials represent one of the primary pillars in developing modern solar cell technologies due to their ability to modify optical and electronic properties at the nanometric level. Consequently, the world is witnessing a significant shift toward clean energy, with solar cells being one of the most prominent of these technologies.This study aims to analyze the latest research (2024/2025) related to the impact of nanostructures (nanoparticles and quantum dots) on improving photovoltaic conversion efficiency.Experimental results were linked to the physical foundations governing solar cell operation. The results indicate that integrating nanostructures can increase practical efficiency by 5-20%, depending on the cell type, offering future prospects for surpassing traditional theoretical limits.